2008
DOI: 10.2139/ssrn.1153985
|View full text |Cite
|
Sign up to set email alerts
|

Emigration Intentions: Mere Words or True Plans? Explaining International Migration Intentions and Behavior

Abstract: Do people follow up on their intentions? In this paper we confront the emigration intentions formed by inhabitants of the Netherlands during the year 2004-2005 and the emigration steps they took in the subsequent two years. Three results stand out. First, it appears that intentions are good predictors of future emigration: 24 percent of those who had stated an intention to emigrate have actually emigrated within two years time. Second, within the group of potential emigrants, those who have emigrated and those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 50 publications
3
112
0
4
Order By: Relevance
“…Van Dalen andHenkens (2008 and and Creighton (2013) showed that migration intentions and aspirations are good predictors of future actual migration behavior. Here we address this concern using the survey question "Have you done any preparation for this move?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Dalen andHenkens (2008 and and Creighton (2013) showed that migration intentions and aspirations are good predictors of future actual migration behavior. Here we address this concern using the survey question "Have you done any preparation for this move?…”
Section: Resultsmentioning
confidence: 99%
“…But a link between actual migration and individual SWB is not investigated here due to lack of access to follow-up interview data. Fortunately, migration intentions and aspirations have been shown to be good predictors of future actual migration behavior (Van Dalen andHenkens 2008 andCreighton 2013) and in the Result section we test the validity of using migration desire for the purposes here. While many researchers use the term "migration intention" to describe future possible migration behavior, we use the term "migration desire" since the main survey question we used is not about planned actions.…”
Section: Introductionmentioning
confidence: 99%
“…The use of data on migratory intentions as a proxy for probability to migrate has now become popular in the literature (Dustmann, 2003;van Dalen et alii, 2005avan Dalen et alii, , 2005bvan Dalen and Henkens, 2008). The justification of this choice of proxy is based on the theory of reasoned action of social psychologists, which looks at a person's intention to undertake certain actions as a function of his or her beliefs about the consequences of his or her actions (Ajzen, 1985;Manski, 1990).…”
Section: / Description Of the Datamentioning
confidence: 99%
“…While an intention to emigrate without any indication of the timing and the strength of the motivation is certainly less informative, we are convinced that an indication of high probability that the respondent will migrate in the next 12 months is much more plausible. Indeed, there is empirical evidence that positive answers to questions aimed at a more definite assessment of the probability to migrate in the very near future, as opposed to a mere statement of desire to migrate, turn out to be good proxies of the actual probability to migrate (Dustmann, 2003;van Dalen et alii, 2005b;van Dalen and Henkens, 2008).…”
Section: / Description Of the Datamentioning
confidence: 99%
“…The reasons are two-fold: first, our data allows for a more robust analysis of intentions rather than behaviour and second, migration intentions are not likely plagued by an endogeneity problem as is migration behaviour allowing for causal inference. While there may be instinctive doubt as to whether intentions approximate actual behaviour, a body of literature suggests plans to migrate are in fact a good, albeit imperfect, predictor of future migration behaviour (Gardner et al, 1985;De Jong, 2000;Van Dalen and Henkens, 2008;Creighton, 2013). Nonetheless, our goal is not to argue whether intentions do robustly predict actual migration behaviour, but to investigate the drivers of those intentions in their own right.…”
Section: Introductionmentioning
confidence: 97%